Status and influencing factors of medication literacy among Chinese caregivers of discharged children with Kawasaki disease - Zhang, Yingzi; Wang, Xiuqiong; Cai, Jianghui; Yang, Yanfeng; Liu, Yiling; Liao, Yeling; Zhou, Yanhong; He, Baoqin; Wen, Wen; Zhuang, Qian; Lin, Yonghong (Frontiers in Public Health, 2022)
Background The information on medication literacy among Chinese caregivers of discharged children with Kawasaki disease (KD) is unknown. We aimed to investigate the status of medication literacy among caregivers of discharged children with KD and evaluate the influencing factors of medication literacy. Methods From March 2020 to February 2021, 106 caregivers with a KD child were recruited for the present study. We collected the sociodemographic characteristics of the KD caregivers using structured interviews. The medication literacy of the KD caregivers was assessed by the Chinese version of Medication Literacy Assessment. KD patients' demographic and clinical data were obtained from the medical records. The multiple logistic regression was performed to identify factors associated with medication literacy. Results (1) The average medication literacy score was 4.91 ± 1.51. (2) Most of the Chinese KD caregivers had insufficient medication literacy (≤ 5 scores), and only 39.2% of the caregivers had adequate medication literacy (>5 scores). (3) The multiple logistic regression shows that education level, monthly income, and duration of hospitalization are the independent influencing factors on the medication literacy of KD caregivers. Conclusion There is preliminary evidence that medication literacy among KD caregivers is low and needs improvement. A higher level of education, higher income, and longer duration of hospitalization were influencing factors of adequate medication literacy.